THE COMPARISON BETWEEN DIRECT METHOD AND GRAMMAR TRANSLATION METHOD IN IMPROVING STUDENTS' READING COMPREHENSION - Debriani Daud; Sukmawati Yasim; Ahmad Munawir (Univeristas Islam Negeri (UIN) Alauddin Makassar, 2022)
The purpose of this research is to find out which method is more effective between the Direct Method and the Grammar Translation Method in improving the reading ability of the students at SMPS Berbudi Kopian. The approach used in this research is quantitative with a quasi-experimental design methodology. The samples are class VIII A students as the Grammar Translation Method class and class VIII B as the Direct Method class. Data were analyzed using the SPSS application. Based on the results of the analysis using SPSS in this study, it was shown that the two methods were slightly improved the students’ reading comprehension at SMPS Berbudi Kopian especially in grade VIII. The results of this study also show that the Grammar Translation Method improves students' reading ability more than using the Direct Method. The results showed that the average post-test in the Direct Method class was 68 and the post-test average in the Grammar Translation Method class was 75. In the table (2-tailed) the independent t-test was more than 0.05 (0.128 > 0.05) it can be concluded that there is no significant difference between student achievement in reading comprehension taught using the Direct Method and Grammar Translation Method. So, the null hypothesis (H0) is accepted.